2017
DOI: 10.1371/journal.pone.0186242
|View full text |Cite
|
Sign up to set email alerts
|

Large (≥3cm) thyroid nodules with benign cytology: Can Thyroid Imaging Reporting and Data System (TIRADS) help predict false-negative cytology?

Abstract: BackgroundThere is controversy about the accuracy of the fine-needle aspiration (FNA) cytology results in large sized thyroid nodules. Our aim was to evaluate the false-negative rate of FNA for large thyroid nodules and the usefulness of the Thyroid Imaging Reporting and Data System (TIRADS) in predicting false-negative cytology for large thyroid nodules with benign cytology.Methods632 thyroid nodules larger than or equal to 3cm in size with subsequent benign cytology on US-guided FNA were included. US feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Larger thyroid nodules (>3 cm) could have higher false-negative rates (~3%) due to larger amounts of background colloid mistaken for benign adenomatous colloid. General recommendations are to consider clinical suspicion, size and suspicious radiological features/TIRADS classification to facilitate surgical decision making (9).…”
Section: Discussionmentioning
confidence: 99%
“…Larger thyroid nodules (>3 cm) could have higher false-negative rates (~3%) due to larger amounts of background colloid mistaken for benign adenomatous colloid. General recommendations are to consider clinical suspicion, size and suspicious radiological features/TIRADS classification to facilitate surgical decision making (9).…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study that evaluated 632 nodules of at least 3 cm found an overall false negative rate of 3.6% that increased from 0.9% to 12% according to the ultrasound risk category. A large variation of false negative rate in nodules of 3 cm or larger has been reported in the literature (0.7-25%) suggesting that various clinical factors, rather than just nodule size, might be related to the diagnostic performance of FNA 147148…”
Section: Estimating the Risk Of Thyroid Cancer And Management After Tmentioning
confidence: 99%
“…Cytology generally shows abundant cellularity and the cells may be typical of the primary site (Chung et al 2012), leading to the correct diagnosis in 74% of cases (Chung et al 2012, Khan et al 2018. However, it exhibits a high false-negative rate in nodules larger than 3 cm (Agcaoglu et al 2013, Nam et al 2017. The most common thyroid metastases for which FNA did not make the correct diagnosis originated from the oesophagus (50%), the cervix (33%), the kidney (28.5%) and melanomas (20%) (Chung et al 2012).…”
Section: Pathologymentioning
confidence: 99%